Monetary policy in the media - Helge Berger; Michael Ehrmann; Marcel Fratzscher (European Central Bank (ECB), 2006)
Media coverage of monetary policy actions is a central channel of a central bank's communication with the wider public, and thus an important factor for its credibility and policy effectiveness. This paper analyses the coverage which ECB monetary policy decisions receive in the print media, and the determinants of its extent and of its favorableness. We find that that the press critically discusses the ECB's policy decisions in the context of prior market expectations and of the inflation environment, and that the media's coverage of decisions is generally highly responsive to ECB communication – in particular its Press Conference on meeting days. However, the paper also finds clear limitations in this regard, thus underlining the critical monitoring role assumed by the media.
Keywords: E52; E58; 330; accountability; communication; coverage; ECB; media; monetary policy; press; transparency; Geldpolitik; Zentralbank; Öffentlichkeitsarbeit; Öffentliche Meinung; Glaubwürdigkeit; Vertrauen; Kommunikationsmedien; Mediennutzung; EU-Staaten